(untitled) (Журнал «Маркетинг», 2024)
The article examines the current trends in the development of the digital economy in Uzbekistan, analyzes the impact of digitalization on various sectors of the economy and public life. Taking into account the global challenges and opportunities associated with the introduction of digital technologies, key government initiatives aimed at supporting digital transformation are being explored, including programs for the development of the IT sector, the creation of digital infrastructure and improved access to Internet services. The paper also discusses the main problems and obstacles faced by businesses and citizens in the process of transition to the digital economy. Based on the analysis of statistical data and examples of successful practices, recommendations for optimizing digitalization processes are presented, as well as proposals for improving public policy in this area. The results of the study emphasize the importance of the digital economy as a driver of economic growth, increasing competitiveness and improving the quality of life of the population of Uzbekistan.